LEGAL DUE TO LEGAL DEFECTS IN THE USE OF POWER (NOTARIIL DEAL) IN THE PROCESS OF TRANSFER RING LAND RIGHTS : (STUDY OF DECISION NUMBER 110/PDT.G/2019/PN.PDG) - Ray Farhan Muhammad (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
This journal discusses the legal defects in absolute power of attorney in the form of a notarial deed. The results of research in the field at this time are still many who use absolute power in various ways, one of which is absolute power used in the process of transferring land rights, where in several regulations, among others, in the Civil Code and Government Regulation Number 24 of 1997 concerning Land Registration. clearly written regarding the prohibition of using absolute power. This study takes the formulation of the problem regarding legal defects in a notarial power of attorney, then the implementation and practice of granting power in a notarial deed and what are the legal consequences of the process of transferring land rights based on a power of attorney in the form of a notarial deed. Keywords: absolute power of attorney, notarial deed, transfer of land rights